The Power and Affiliation Component of Achievement Pride: Antecedents of Achievement Pride and Effects on Academic Performance - Buechner, Vanessa Laura; Stahn, Veronika; Murayama, Kou (Frontiers in Education, 2019)
Previous research on the self-conscious achievement emotion pride introduces the Achievement Pride Scales (APS) that illustrate the relation of self-based pride and social comparison-based pride with frames of reference, achievement goals, and achievement values. The present study (N = 354) extends those results with regard to explicit achievement, affiliation, and power motives, as well as performance. Results show that self-based pride is related to self-approach goals, individual achievement values, as well as achievement and affiliation motives. Social comparison-based pride, in turn, is positively related to other-approach goals, social achievement values, as well as achievement and power motives. In addition, when controlling for those antecedent variables a positive effect of social comparison-based pride on academic performance disappears whereas a positive effect of self-based pride on academic performance appears. As such, the present work replicates and broadens the knowledge on achievement pride.